Comparative Analysis and Considerations on the Current Development and Future Trends of Children's Museums in Korea and China (Journal of Global Arts Studies, 2023)
Background: Children's museums play a crucial role in childhood education, with an inherent connection to the future development of a nation. Objective: Children's museums in South Korea and China differ in culture, display, education, etc., each with its own strengths. Reciprocal learning can enhance the development of these museums, acting as a conduit for international cultural exchange and cooperation, fostering global cultural interaction. Methods: Through extensive literature analysis, this paper compares and analyzes the development, quantity, exhibition, educational status, and future trends of children's museums in Korea and China. It discusses the similarities and differences, as well as the challenges faced by children's museums in both countries. Results: The study reveals the following: 1) Cultural differences have shaped the unique historical features of children's museums' development in Korea and China. 2) There is a noticeable disparity in the number of children's museums between the two countries. 3) Korean and Chinese children's museums share similarities in exhibition and education, yet there are notable differences. 4) The future development trajectories for the two countries vary. Conclusion: Korea and China are geographically and culturally proximate. This research, by comparing the historical development, current state, exhibition, and educational aspects, as well as the future trends of children's museums in these countries, aims to provide beneficial insights for the development of children's museums and cultural exchanges.
Keywords: Children's Museums, Exhibition Methods, Children's Education, Cultural Differences